Temporal changes in habitat structure and gastropod community assemblage in response to active restoration of a Central American mangrove - López-Abuchar, Linda; Peralta-Madriz, Christian; Soto-Navarro, Carolina; Vinueza-Hidalgo, Gabriela; Whitworth, Andrew; Beirne, Christopher (Frontiers in Marine Science, 2025)
Mangrove forests are biodiversity hotspots that provide critical ecosystem services, from coastal protection to carbon storage. Yet, these ecosystems are disappearing at alarming rates, and while restoration efforts are expanding globally, long-term monitoring—especially in the Americas—remains scarce and often narrowly focused on vegetation structure, overlooking biological recovery. In this study, we evaluate whether gastropod community assemblages can serve as functional indicators of ecological recovery across different stages of mangrove restoration in Costa Rica. Using a space-for-time approach, we compared tree structure and gastropod assemblages across restored sites of varying ages, unrestored areas, and mature mangrove forests. We applied linear mixed models to examine how restoration stages influenced structure (tree height and DBH) and biodiversity metrics (gastropod abundance and composition). Tree structure improved consistently with restoration age, with five-year-old trees reaching nearly half the height and DBH of mature forest counterparts. Gastropod abundance exhibited a non-linear response—initially declining post-planting, then peaking by year five. Community composition also shifted: Melampus dominated early stages, while older sites supported Vitta, Cerithideopsis, and Littoraria. The exclusive presence of Thaisella in mature forests suggests its potential as a bioindicator of late-stage ecological recovery. Our results underscore the value of integrating biological indicators into mangrove monitoring. Gastropod assemblages offer a powerful lens through which to monitor ecological functionality, providing a low-cost, scalable tool to enhance adaptive management and guide future restoration efforts in tropical coastal ecosystems.